Progress in Volcanology - Paone, Angelo; Yun, Sung-Hyo (IntechOpen, 2022)
Progress in Volcanology includes nine chapters in three sections. The first section is the "Introduction" while the other two sections speak on "Applied Volcanology" and "Volcanic Sedimentology, Geochemistry and Petrology." The chapters address volcanology in several areas around the world, including Italy, Indonesia, Ethiopia, Argentina, India, and others.